Plasma cell numbers decrease in bone marrow of old patients. Issue 3 (23rd December 2014) - Pritz, Theresa; Lair, Julian; Ban, Michael; Keller, Michael; Weinberger, Birgit; Krismer, Martin; Grubeck‐Loebenstein, Beatrix
<x xml:space="preserve">Abstract</x> The BM is well understood to play a key role in plasma cell homing and survival in mice. In humans, BM plasma cells and their functions are less well characterized. In this study, we used paired bone biopsies from the femur shaft and blood samples from persons of different ages to analyze age‐related changes of plasma and memory B cells. Our results demonstrated that plasma cells were mainly located in the BM, while a higher percentage of memory B cells was in the peripheral blood than in the BM. The frequency of plasma and memory B cells from both sources decreased with age, while immature and naïve B cells were unaffected. An age‐related decline of tetanus‐ and diphtheria‐specific BM plasma cells was observed, whereas influenza A‐ and cytomegalovirus‐specific BM plasma cells were not affected. With the exception of cytomegalovirus, peripheral antibody concentrations correlated with BM plasma cells of the same specificity, but were independent of antigen‐specific peripheral blood memory B cells. Our results demonstrate that the BM houses decreased numbers of plasma cells in old age. The number of cells of certain specificity may reflect the number and time point of previous antigen encounters and intrinsic age‐related changes in the BM.